Sexual orientation in forensic settings - Natale, Anthony P. (Handbook of forensic social work, 2024)
The chapter’s author aims to provide definitions and examples for key terms relative to lesbian, gay and bisexual (LGB) people and the oppression resulting from societal response to sexual orientation. Next, an overview of the rates and trends of LGB engagement with forensic institutions is provided. Then, he provides an overview of constitutional and legislated rights that impact LGB people in forensic settings are reviewed. The LGB prison pipeline is discussed in detail next. The author closes the chapter with a listing of crucial reforms needed relative to LGB experiences with forensic settings, along with a discussion of critical strategies for social workers to engage in to accomplish these goals.